POVERTY, POLICY AND PLAQUE: RETHINKING ORAL HEALTH IN A LOW-INCOME POPULATION (Journal of Medical & Health Sciences Review, 2025)
Background: Oral health remains a neglected component of public health in Pakistan, despite high prevalence of preventable oral diseases and their substantial impacts on daily functioning and quality of life. Evidence on how low-income communities experience, prioritize, and navigate oral health challenges particularly in marginalized regions such as Khyber Pakhtunkhwa is limited.Objective: This study explored lived experiences of oral health, perceived barriers to dental care, and perceptions of public oral health services among low-income populations in Khyber Pakhtunkhwa, Pakistan.Methods: A qualitative exploratory design was employed, including 4 focus group discussions and 20 in-depth interviews with purposively selected adults and key informants. Data were analyzed thematically using an inductive approach, guided by a social determinant of health framework.Results: Oral health problems, including toothache, gum disease, and tooth loss were widely normalized and deprioritized due to poverty, competing survival needs, and limited awareness. Financial constraints, transportation costs, and reliance on private dental care resulted in delayed care-seeking and preference for tooth extraction over restorative treatment. Women faced compounded barriers due to restricted mobility, financial dependence, and caregiving responsibilities. Public oral health services were perceived as inaccessible, inadequately equipped, and extraction focused. These findings resonate with national epidemiological data indicating high prevalence of untreated dental caries and periodontal disease among socioeconomically disadvantaged groups. Conclusion: Oral health inequities in low-income communities of Khyber Pakhtunkhwa are embedded in structural poverty, gender norms, and weak policy prioritization. Addressing these inequities requires integrating oral health into primary healthcare, social protection programs, and universal health coverage reforms, alongside strengthening public services and implementing equity-oriented, preventive strategies.